Raman spectroscopic analysis of paddy rice infected by three pests and diseases common in Northeast Asia. (October 2019) - Yue, Xin; Tan, Yong; Fan, Wenzhong; Song, Shaozhong; Ji, Hongyu; Li, Bingbing
Abstract: Pests and diseases seriously affect the yield and economic benefits of growing rice, and the key to inhibiting rice's pathogenesis is to find early identification of rice infection. The characteristic Raman spectrum of healthy leaves, and leaves infected with rice blast, paddy rice bakanae and infected by Chilo suppressalis (Walker) were tested by TriVista555CRS laser Raman spectrometer (900cm −1 –1700cm −1 ). At the same integration time, compared with healthy plants, the Raman peak of infected plants not only changed significantly, but also the signal intensity decreased. The results show that there are clear Raman peaks at the three characteristic wavenumbers of 1002.87cm −1, 1156.5cm −1 and 1522.36cm −1 . Especially in the leaves of rice blast, it was found that the degree of fungal infection affects the peak width at half height of the characteristic peak. The research shows that Raman spectroscopy provides an effective method for the early detection of rice pests and diseases which may have economic benefits.